Free Play of Imagination in Art to Make Meaning in Pain: A Comparative Study of Nabokov’s Invitation to a Beheading and Dogville - Leili Kafi; Kian Soheil (مطالعات بین‌رشته‌ای ادبیات، هنر و علوم انسانی)
By focusing on pain as a phenomenon that deprives individuals of meaning, the present study illuminates how the free play of imagination in art is able to defy pain and help individuals attain meaning. As an interdisciplinary research in literature and cinema and through a comparative approach, this study applies Scarry’s notion of pain in The Body in Pain, the Making and Unmaking of the World to Nabokov’s Invitation to a Beheading (1935) and Von Trier’s Dogville (2003). To do so, first Scarry’s definition of pain (torture) in physical and verbal act is presented. Then disruption of meaning by pain is discussed. Third, the transformative role of pain is explained to show how pain can embed in itself ways to pass through pain. Finally, the free play of imagination (art) is discussed to clarify whether and how it can help attain meaning in pain. Through close reading, these definitions and notions are applied to the selected works and especially to their main characters, Cincinnatus and Grace. In conclusion it is asserted that Nabokov and Von Trier, although different artists in the first glance, share notable grounds in their oeuvre. Enjoying Brechtian alienation, game play, parody and complex defamiliarizing narration, they create a diegetic world surpassing ideological, social and psychological issues encompassing characters/events that are not clear copies of reality but the result of the free play of imagination to undo the annihilating power of pain.